2018
DOI: 10.1242/bio.029603
|View full text |Cite
|
Sign up to set email alerts
|

Concerted evolution of body mass and cell size: similar patterns among species of birds (Galliformes) and mammals (Rodentia)

Abstract: Cell size plays a role in body size evolution and environmental adaptations. Addressing these roles, we studied body mass and cell size in Galliformes birds and Rodentia mammals, and collected published data on their genome sizes. In birds, we measured erythrocyte nuclei and basal metabolic rates (BMRs). In birds and mammals, larger species consistently evolved larger cells for five cell types (erythrocytes, enterocytes, chondrocytes, skin epithelial cells, and kidney proximal tubule cells) and evolved smaller… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(48 citation statements)
references
References 53 publications
2
45
1
Order By: Relevance
“…We should also consider here that cell size and, thus, the total area of plasma membranes in tissue might not affect metabolic performance if animals are studied in their resting state, as was the case here. In contrast to our findings, some previous studies have demonstrated an inverse relationship between cell size and metabolic rate (e.g., Chown et al., 2007; Czarnoleski et al., 2018; Hermaniuk, Rybacki, & Taylor, 2017; Maciak et al., 2014; Starostová et al., 2013; Starostová, Kubička, Konarzewski, Kozłowski, & Kratochvíl, 2009). Also against the pattern revealed here for P. scaber , comparisons of thermal sensitivity of Carabidae beetles showed that large species were characterized by higher metabolic responses to thermal change than small species (Gudowska, Schramm, Czarnoleski, Kozłowski, & Bauchinger, 2017).…”
Section: Discussioncontrasting
confidence: 99%
“…We should also consider here that cell size and, thus, the total area of plasma membranes in tissue might not affect metabolic performance if animals are studied in their resting state, as was the case here. In contrast to our findings, some previous studies have demonstrated an inverse relationship between cell size and metabolic rate (e.g., Chown et al., 2007; Czarnoleski et al., 2018; Hermaniuk, Rybacki, & Taylor, 2017; Maciak et al., 2014; Starostová et al., 2013; Starostová, Kubička, Konarzewski, Kozłowski, & Kratochvíl, 2009). Also against the pattern revealed here for P. scaber , comparisons of thermal sensitivity of Carabidae beetles showed that large species were characterized by higher metabolic responses to thermal change than small species (Gudowska, Schramm, Czarnoleski, Kozłowski, & Bauchinger, 2017).…”
Section: Discussioncontrasting
confidence: 99%
“…Kozłowski et al (2010) found support for such concerted changes at the interspecific level in birds and amphibians, although in mammals, not all cell types changed in complete synchrony. A comparative study of species of galliforms and rodents showed that larger species consistently evolved larger cells of five cell types (erythrocytes, enterocytes, chondrocytes, skin epithelial cells, and kidney proximal tubule cells) and smaller hepatocytes (Czarnoleski et al, 2018). Savage et al (2007) reported diverse interspecific relationships between body mass and the size of different cell types in mammals by applying a phylogenetically noninformed analysis.…”
Section: Mechanistic Explanation Of Hypoallometric Mr Scalingmentioning
confidence: 99%
“…The genes that control these pathways in flies are differentiated along latitudinal clines in conjunction with cell size and body size (De Jong & Bochdanovits, 2003). The activities of such pathways also explain coordinated cell size changes in different tissues during evolutionary differentiation of species of mammals, birds and amphibians (Kozłowski et al ., 2010; Czarnoleski et al ., 2018). A ubiquitous correlation between nucleus size and cell size, which is visible at intraspecific (Maciak et al ., 2014) and interspecific levels (Kozłowski et al ., 2010), suggests the involvement of a cytological mechanism in cell size regulation.…”
Section: Mechanistic Explanation Of Hypoallometric Mr Scalingmentioning
confidence: 99%
“…Variation in body mass can result from changes in cell number, cell size or a combination of both [39,40], but usually larger-bodied species tend to have larger cells, as documented in arthropods [40,41], fish [42] and birds and mammals [43]. The theory of optimal cell size [44] highlights how differences in cell size have repercussions for oxygen uptake at the cellular level.…”
Section: Introductionmentioning
confidence: 99%